Phytochemical Screening and Antibacterial Activity of Ethanolic Extract of Syzygium samarangense Leaves - Nur Amalia Choironi; Muhamad Salman Fareza (Jurnal Kartika Kimia, 2018)
The ethanolic extracts of S. samarangense leaves were examined for antibacterial activity in vitro using broth microdillution method. The extracts showed effective against Bacillus cereus, Salmonella enterica with MIC (minimum inhibition concentration) value 78 µg/ml and against multi strains of Escherichia coli, Enterobacter aerogenes, Kocuria rhizophila with MIC value 2500 µg/mL, 2500 µg/mL and 156 µg/mL. Phytochemical screening of S. samarangense was observed for the presence of tannins, alkaloids, flavonoids, and terpenoids.